A more expansive perspective on translation in IB research: Insights from the Russian Handbook of Knowledge Management - Holden, Nigel J; Michailova, Snejina (Journal of International Business Studies, 2014)
The treatment of translation in the international business (IB) literature has been predominantly concerned with research methodology and back-translation. Arguing for a less microscopic concept of translation in IB research, we advocate a more expansive perspective, whereby translation is understood as cross-border interplay of entire terrains of corporate contexts and experience linking multiple mental and social frames of reference. We apply three notions from linguistics and translation studies – equivalence, ambiguity and cultural interference – to problematize the translation of management terms and concepts across languages and to highlight the importance of historical and cultural embedding in the translation process. We substantiate the core argument through analysis of fragments from Russia’s first Handbook of Knowledge Management, a text composed of 23 contributions translated from English into Russian, a language in restless regeneration, struggling arduously with Western management terms and concepts after 70 years of communism. This knowledge management text constitutes the essence of an entire corpus of modern management thought and action which is largely unfamiliar to the Russian business and scholarly community. We demonstrate how acts of translation serve as an analog for the cross-cultural transfer of knowledge and how these insights can advance IB translation research into new and rewarding directions.